2005
DOI: 10.1089/hyb.2005.24.141
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of a Specific Monoclonal Antibody Against CIAPIN1

Abstract: Cytokine-induced antiapoptosis inhibitor 1 (CIAPIN1) is a newly identified antiapoptosis molecule and a mediator of gastric MDR. We cloned cDNA of human CIAPIN1 by RT-PCR and constructed prokaryotic expression vectors of human CIAPIN1 by inserting human CIAPIN1 coding region into pET28-a(+) and pGEX- 4T-1, respectively. The fusion proteins were expressed in Escherichia coli and purified by affinity chromotography. Monoclonal antibody (MAb) against CIAPIN1 was obtained with standard cell fusion technique and EL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 11 publications
0
26
0
Order By: Relevance
“…Immunohistochemistry was performed using the mouse monoclonal antibody (mAb) against CIAPIN1 (clone 3C6) produced by our laboratory as described elsewhere 9 and Histostain TM -Plus SP kit (ZYMED, USA.). Briefly, the sections were deparaffinized with xylane and rehydrated through gradient ethanol emmersion.…”
Section: Reduced Ciapin1 Contributes To Gastric Carcinogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemistry was performed using the mouse monoclonal antibody (mAb) against CIAPIN1 (clone 3C6) produced by our laboratory as described elsewhere 9 and Histostain TM -Plus SP kit (ZYMED, USA.). Briefly, the sections were deparaffinized with xylane and rehydrated through gradient ethanol emmersion.…”
Section: Reduced Ciapin1 Contributes To Gastric Carcinogenesismentioning
confidence: 99%
“…In previous studies on multidrug resistance (MDR) of gastric cancer, we found that the expression of CIAPIN1 was upregulated at both mRNA and protein levels in gastric cancer cell lines SGC7901/VCR and SGC7901/ADR, which are multidrug resistant, compared with that in their non-resistant parental cell line SGC7901. 8,9 Moreover, ectopic expression of CIAPIN1 in SGC7901 leads to MDR whereas knockdown of CIAPIN1 by small interference RNA (siRNA) sensitizes SGC7901/ADR to antitumor chemotherapeutic drugs, indicating that CIAPIN1 is a mediator of gastric cancer MDR. 10 In the study carried out by Shibayama et al Ras activators IL-3, EPO, SCF (c-Kit) and TPO induced mCIAPIN1 expression and oncogenic H-Ras (H-RasG12V) induced the expression of CIAPIN1, whereas dominant-negative H-Ras (HRasS17N) reduced the expression of mCIAPIN1, suggesting that CIAPIN1 is a downstream molecule of receptor tyrosine kinase-Ras signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…11 Our previous studies about multidrug resistance (MDR) of gastric cancer revealed that expression of CIAPIN1 was upregulated in MDR gastric cancer cell subline SGC7901/ ADR and SGC7901/VCR both at mRNA and protein levels, 12,13 and CIAPIN1 confered MDR in gastric cancer cells possibly by upregulating multidrug resistance gene-1 (MDR-1) and multidrug related protein-1 (MRP-1) expression. 14 In addition, our study showed that CIAPIN1 is ubiquitously expressed in both fetal and adult tissues, with higher expression in differentiated tissues and tissues with active metabolism, suggesting that CIAPIN1 might perform a common and possibly important function in human tissues.…”
Section: Introductionmentioning
confidence: 99%
“…endogenous peroxidase activity was blocked by incubation with 3% hydrogen peroxide for 10 min and rinsed in pBs. the slips were incubated with anti-cIApIn1 primary mouse monoclonal antibody (developed by Hao et al) overnight at 4˚C (10). Histostain™-Plus kits (Zhongshan, china) were used according to the manufacturer's instructions for detection of cIApIn1.…”
Section: Methodsmentioning
confidence: 99%